Financial-monetary instability factors within the framework of the recent crisis in Romania - Bogdan Florin Filip (Romanian Academy, National Institute for Economic Research, 2014)
The paper starts from the premise of the organic integration of the financialmonetary components, with their corresponding interrelations, within the macroeconomic system and from their role in ensuring the normal operation of the entire system. In this respect, it is invoked the impact of some financial-monetary components' functioning, with possible malfunctions reflected on the economic stability, and specific factors that determine financialmonetary instability. The development of research focuses on the analysis of some relevant manifestations of financial-monetary instability, marked by major imbalances expressed themselves, synthetically, through high variations of some specific indicators: inflation rate, bank loans interest rate, foreign exchange rate, etc. In this framework, most of the paper consists in econometric analysis, made through the prism of relations of determining that involve main factors generating financial-monetary instability, on the background of the conditions in Romania, in 2008-2013. There are taken so into calculations data for the previously mentioned indicators, considered as dependent variables, on the one hand, respectively those representing GDP, the NPLs volume, M2 monetary aggregate etc., considered as determinant factors and variables, on the other hand. On this basis, there are outlined conclusions and suggested some possibilities to counteract the financial-monetary instability.
Keywords: C23; E63; G01; 330; Financial Monetary Imbalances; Inflation Rate; Exchange Rate; Interest Rate On Bank Loans; Non-Performing Loans